Matviishin E.M. Tribotechnical properties of electroarc metallic coverages from pseudoalloys as Fe-Cu-Al. - Матвіїшин, Є.М. (Problems of Tribology, 2014)
In this work investigation tribo technical and properties of durability of pseudoalloys, nebulized by electro-arc method with the use of composite Fe-Cu and continuous aluminium wire. In the process of leadthrough of researches determined their firmness against a wear in the conditions of friction of sliding at the limited serve of greasing and high contact pressures, and also propensity to development of grasping processes after stopping of serve of greasing. Properties of durability of the nebulized layers were estimated on results measuring of their hardness, durability of tripping with the surface of good and size of internal tensions in coverages. It was set that three component Fe-Cu-Fl coverages differ the best tribo by technical properties as compared to two by the component Fe-Al pseudoalloys, nebulized composite wires, and also greater durability of tripping and less in size internal tensions. It allows to inflict the layers of considerable thickness on the flat and concave surfaces of wares and provide their reliable work at high pressures in the area of contact of the attended surfaces. Comparative tests of capacity of the cast bronzes, and also standards with metallization bronze layers and coverages from the pseudoalloy of type of Fe45Cu15Al40 rotined that napylennye bronze coverages had in 1,5 - 2,4 time more high wearproofness as compared to the cast bronzes, and three-component pseudoalloys have in 6 - 12 times less losses at a wear by comparison to the cast bronze of Br OCS 4-3.